Centre of resistance and centre of rotation of a tooth: experimental determination, computer simulation and the effect of tissue nonlinearity. Issue 3 (17th February 2016) - Nyashin, Y.; Nyashin, M.; Osipenko, M.; Lokhov, V.; Dubinin, A.; Rammerstorfer, F.; Zhurov, A.
Abstract : The centre of resistance and centre of rotation of a tooth are key concepts in orthodontics. Determining the coordinates of these points is essential for planning orthodontic tooth movement. The paper proposes a procedure for experimental determination of the two centres, verifies a previously developed mathematical theory through computer simulations and evaluates the effect of nonlinearity of the periodontal ligament on the parameters related to the centres. The paper relies on the mathematical theory of a rigid body embedded in an elastic medium, physical experiment, finite element method and a simple nonlinear theory of the tooth. The concept of the centre of resistance requires a revision if nonlinearity is taken into account.